DESCRIPTION OF THE SELF ADJUSTMENT STUDENTS COMING FROM OUTSIDE THE PADANG CITY - Erfan Ramadhani (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2018)
ABSTRACT This research is intended to reveal students who are from outside the city of Padang. This research uses qualitative with descriptive method through collecting data with interviews, observation, and documentation. After the data is obtained then it is done by using the steps as follows, Data Reduction, Data Presentation, and Conclusion Drawings. The informants of this study were one person from outside the city of Padang and one person from the city of Padang. The results of this study are: 1) on indicators that discuss personal difficulties that are difficult to understand, 2) on indicators of social communication prepared about difficult time in socializing. Suggestions in this study are expected for migrants to be able to socialize well and are expected to be able to speak the new language, so that communication can continue. Keywords: Self-Adjustment, Outside the City of Padang